Creation of a Collaborative “School–University” Environment to Support Research Activities in Schools - Saule Begaliyeva; Elena Shmakova; Assel Zhunisbayeva (Education Sciences)
This study identifies the issue of insufficient scientific and methodological support for school research projects. To address this, the study proposes the creation of a collaborative “school–university” environment, enabling schoolteachers and students to receive necessary guidance and methodological assistance in preparing and implementing school research projects in the humanities. The study suggests leveraging the Digital Humanities field to incorporate modern digital tools for creating competitive research projects that meet not only the requirements of the Ministry of Education, but also global scientific and economic trends. The assessment of the current situation in the preparation and implementation of school projects involved a survey of more than 600 teachers from the southern region of Kazakhstan. The survey results reveal that over 80% of teachers require scientific and methodological support in preparing school research projects. Based on the survey findings and the expressed demand for methodological assistance, the development of a pilot digital platform is planned. This platform will facilitate collaborative work among schoolteachers, students, university professors, and gifted students to create research projects in Digital Humanities. Such collaborative efforts aim to address the lack of adequate preparation for school research projects.